2012
DOI: 10.5796/electrochemistry.80.898
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution Rate of Noble Metals for Electrochemical Recycle in Polymer Electrolyte Fuel Cells

Abstract: An electrochemical recycling process of the noble metal such as Pt and Ru from the membrane electrode assemblies (MEAs) in fuel cells was investigated for the environment-friendly process without aqua regia. The dissolution rate of Pt in HCl solution was about 50 times as fast as those in H 2 SO 4 and HClO 4 solutions. The Pt dissolution rate increased linearly with HCl concentration. Pt dissolution under fluctuating potential using saw-tooth wave is 15 times faster than that under constant potentials. The ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Many hydrometallurgical approaches also require high operating temperatures and pressures, making them energy intensive processes. Pyrometallurgical processes for PEMFCs containing fluorinated membranes such as Nafion would result in the emission of highly toxic hydrogen fluoride 175,176 . The Pt/C catalyst can also be recovered using a chemical recovery process after carbon-based supports are incinerated 175,176 .…”
Section: Recycling Of Pemfcsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many hydrometallurgical approaches also require high operating temperatures and pressures, making them energy intensive processes. Pyrometallurgical processes for PEMFCs containing fluorinated membranes such as Nafion would result in the emission of highly toxic hydrogen fluoride 175,176 . The Pt/C catalyst can also be recovered using a chemical recovery process after carbon-based supports are incinerated 175,176 .…”
Section: Recycling Of Pemfcsmentioning
confidence: 99%
“…Pyrometallurgical processes for PEMFCs containing fluorinated membranes such as Nafion would result in the emission of highly toxic hydrogen fluoride 175,176 . The Pt/C catalyst can also be recovered using a chemical recovery process after carbon-based supports are incinerated 175,176 . Generally, alloying and non-combustible elements consisting of 10% or less of the total recoverable materials will not detrimentally affect recoverability or reusability of precious metal catalysts 128 .…”
Section: Recycling Of Pemfcsmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] As the platinum is already immobilized on the electrode, its electrochemical dissolution seems to be promising and would avoid the use of oxidants such as HNO 3 . [17] As the platinum is already immobilized on the electrode, its electrochemical dissolution seems to be promising and would avoid the use of oxidants such as HNO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Shiroishi et al have adapted an electrochemical dissolution method to recover Pt and Ru from PEFCs. 13) They apply potentiodynamic electrolysis to dissolve noble metals from Pt-loaded electrodes using several potential wave pro les and have shown that a saw-tooth wave is 15 times faster than constant potentials are. In order to adapt the electrochemical dissolution method to actual fuel cells, it is necessary to con rm the dissolution of Pt metal from MEAs.…”
Section: Introductionmentioning
confidence: 99%